2021
DOI: 10.3389/fonc.2021.781720
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of Iron Homeostasis in the Induction of Mitochondrial Apoptosis by 6-Gingerol Through PTEN Regulated PD-L1 Expression in Embryonic Cancer Cells

Abstract: Embryonic cancer stem cells (CSCs) can differentiate into any cancer type. Targeting CSCs with natural compounds is a promising approach as it suppresses cancer recurrence with fewer adverse effects. 6-Gingerol is an active component of ginger, which exhibits well-known anti-cancer activities. This study determined the mechanistic aspects of cell death induction by 6-gingerol. To analyze cellular processes, we used Western blot and real-time qPCR for molecular signaling studies and conducted flow cytometry. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Recurrence of cancer is a major complication in various chemotherapeutic drugs because although it effectively suppresses tumor growth, it may fail to target CSCs [ 28 ]. This issue makes research on natural anticancer compounds an attractive method because such compounds can be used for long-term exposure as they reduce side effects and can help target both cancer cells and CSCs [ 29 , 30 ]. There are a few natural compounds that have the potential to work against CSCs [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence of cancer is a major complication in various chemotherapeutic drugs because although it effectively suppresses tumor growth, it may fail to target CSCs [ 28 ]. This issue makes research on natural anticancer compounds an attractive method because such compounds can be used for long-term exposure as they reduce side effects and can help target both cancer cells and CSCs [ 29 , 30 ]. There are a few natural compounds that have the potential to work against CSCs [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 is implicated in maintenance of the balance between Th17 and Treg cells in patients following gastric cancer resection via the PD-1/PD-L1 pathway [11]. Moreover, PTEN induction has been found to reduce miR-21 expression, thus resulting in downregulation of PD-L1 via the PI3K/Akt/ p53 signaling pathway in embryonic cancer stem cells [30]. Accordingly, our experimental results suggested that miR-21 induced PD-L1 expression via the PI3K/Akt pathway activation by targeting PDCD4 in BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) can impede mRNA translation and increase mRNA breakdown, resulting in post-transcriptional gene expression changes. By interacting with PD-L1, these miRNAs also have a role in the tumor immune system [36]. As a result, miR-34a and miR-200c are linked to PD-L1 production in response to p53-dependent antitumor actions [37,38].…”
Section: Introductionmentioning
confidence: 99%